The role of retinal vessel geometry as an indicator of systemic arterial stiffness assessed by cardio-ankle vascular index - Ma, Dae Joong; Lee, Heesun; Choi, Ji Min; Park, Hyo Eun; Choi, Su-Yeon; Choi, Hyuk Jin (Frontiers in Cardiovascular Medicine, 2023)
Objective To determine whether retinal vessel geometry is associated with systemic arterial stiffness, as determined by the cardio-ankle vascular index (CAVI). Methods This single-center retrospective cross-sectional study included 407 eyes of 407 subjects who underwent routine health exams, including CAVI and fundus photography. Retinal vessel geometry was measured using a computer-assisted program (Singapore “I” Vessel Assessment). Subjects were classified into two groups based on CAVI values: high CAVI (≥9) or low CAVI (<9). The main outcome measures included the association of retinal vessel geometry and CAVI value evaluated using multivariable logistic regression models. Results Three hundred forty-three subjects (343, 84.3%) were in the low CAVI group, and 64 (15.7%) subjects were in the high CAVI group. Multivariable logistic linear regression analyses adjusted for age, sex, body mass index, smoking status, mean arterial pressure, and the presence of hypertension, diabetes mellitus, and dyslipidemia showed a significant association between high CAVI values and the following retinal vessel geometry parameters: central retinal arteriolar equivalent caliber (CRAE; adjusted odds ratio [AOR], 0.95; 95% confidence interval [CI], 0.89–1.00; P = 0.043), fractal dimension of arteriolar network (FDa; AOR, 4.21 × 10−4; 95% CI, 2.32 × 10−7−0.77; P = 0.042), and arteriolar branching angle (BAa; AOR, 0.96; 95% CI, 0.93–0.99; P = 0.007). Conclusions Increased systemic arterial stiffness had a significant association with retinal vessel geometry related to arterial narrowing (CRAE), less branching complexity of the arterial tree (FDa), and acute arteriolar bifurcation (BAa).